Pengaruh Leverage Dan Kebijakan Dividen Terhadap Pertumbuhan Laba Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Debi Eka Putri; Anggraini Syahputri; Herlina Theodensia D. Doke; Hermanus Reo; Liper Siregar (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
Objective. This research aims to understand how leverage and dividend policy influence the profit growth of food and beverage sub-sector companies listed on the Indonesia Stock Exchange during 2018-2021. Research Method. In this research, the purposive sampling method was used to select 10 companies. Data analysis techniques involve classical assumption testing, multiple linear analysis, correlation and determination coefficients, and hypothesis testing. Results. The effect of leverage on profit growth is not significant, while dividend policy has a significant effect on profit growth. Conclusion. It is advised that corporate aware to using debt more wisely and increase profit generation in order to increase profit growth.